Leadership Styles and Organisational Performance in Nigeria: Qualitative Perspective - Akpa, Victoria O.; Asikhia, Olalekan U.; Okusanya, Adedoyin, O. (International Journal of Engineering and Management Research, 2021)
Organizations in different sectors of the Nigerian economy continue to record high cases of misappropriation, embezzlement, immoral and unethical practices, gratifications, high labour turnover, inability to meet basic required obligations, and employees’ dissatisfaction, which have further resulted in poor performance. The theoretical paper dwelled on the concepts of leadership styles as opined by several scholars in the literature and used these as springboards to arrive at elaborate ones that encapsulated all and introduced a range of common and contemporary models and approaches, including an addition of a cutting-edge competitive list to help managers discover, devise and adjust their individual management practice and style for navigation towards a sustainable organizational performance.